2009
DOI: 10.1590/s1516-89132009000600027
|View full text |Cite
|
Sign up to set email alerts
|

Sperathe effects of solid-state fermentation in the functional properties of defatted rice bran and wheat bran

Abstract: Functional properties of fermented bran produced by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…These results are of practical feeding importance because NDICP is slowly degraded in the rumen and constitutes a major portion of the ruminal undegraded protein content [48]. These results agree with those of Silveira and Badiale-Furlong [49] and Ranjan et al [50], who found a decrease in CP digestibility in these fermented products, and Nicolini et al [51] who found a decrease in the in vitro true digestibility of fermented orange peels.…”
Section: Discussionsupporting
confidence: 83%
“…These results are of practical feeding importance because NDICP is slowly degraded in the rumen and constitutes a major portion of the ruminal undegraded protein content [48]. These results agree with those of Silveira and Badiale-Furlong [49] and Ranjan et al [50], who found a decrease in CP digestibility in these fermented products, and Nicolini et al [51] who found a decrease in the in vitro true digestibility of fermented orange peels.…”
Section: Discussionsupporting
confidence: 83%
“…The physicochemical composition and particle size distribution of wheat bran used in this study was characterized and summarized in Lonsane (1994) and Silveria and Badiale-Furlong (2009). Approximately 54% of the wheat bran had the size of 150-250 m and 43% had the size of 250-500 m.…”
Section: Wheat Bran Characterizationmentioning
confidence: 99%
“…Fermentation technology can increase protein content in agricultural products and agro-industrial wastes through growth and activity of microbial metabolism [8][9][10][11][12][13][14]. Fermentation can also improve nutrients, aroma, flavor, and texture through enzymatic activity produced by microbes that can be used as functional food [15,16].…”
Section: Introductionmentioning
confidence: 99%